Preoperative bisphosphonate treatment may adversely affect the outcome after shoulder arthroplasty. (February 2019) - Mai, D. H.; Oh, C.; Doany, M. E.; Rokito, A. S.; Kwon, Y. W.; Zuckerman, J. D.; Virk, M. S.
Abstract : Aims: The aim of this study was to investigate the effects of preoperative bisphosphonate treatment on the intra- and postoperative outcomes of arthroplasty of the shoulder. The hypothesis was that previous bisphosphonate treatment would adversely affect both intra- and postoperative outcomes. Patients and Methods: A retrospective cohort study was conducted involving patients undergoing arthroplasty of the shoulder, at a single institution. Two patients with no previous bisphosphonate treatment were matched to each patient who had received this treatment preoperatively by gender, age, race, ethnicity, body mass index (BMI), and type of arthroplasty. Previous bisphosphonate treatment was defined as treatment occurring during the three-year period before the arthroplasty. The primary outcome measure was the incidence of intraoperative complications and those occurring at one and two years postoperatively. A total of 87 patients were included: 29 in the bisphosphonates-exposed (BP + ) group and 58 in the non-exposed (BP - ) group. In the BP + group, there were 26 female and three male patients, with a mean age of 71.4 years (51 to 87). In the BP - group, there were 52 female and six male patients, with a mean age of 72.1 years (53 to 88). Results: Previous treatment with bisphosphonates was positively associated with intraoperative complications (fracture; odds ratio (OR) 39.40, 95% confidence interval (CI) 2.42 to 6305.70) and one-year postoperative complications (OR 7.83, 95% CI 1.11 to 128.82), but did not achieve statistical significance for complications two years postoperatively (OR 3.45, 95% CI 0.65 to 25.28). The power was 63% for complications at one year. Conclusion: Patients who are treated with bisphosphonates during the three-year period before shoulder arthroplasty have a greater risk of intraoperative and one-year postoperative complications compared with those without this previous treatment.